(untitled) (Research, Society and Development, 2021)
The research aimed to analyze the antimicrobial potential of silver nanoparticles stabilized in curcumin and cashew (Anacardium occidentale L) leaf extract. In the methodology, silver nanoparticles (AgNPs) were synthesized from 125 mL of silver nitrate (AgNO3) at boiling under magnetic stirring and dripping with 5 mL of 1% sodium citrate, and stabilized in curcumin and cashew extract. Antimicrobial tests were performed against Staphylococcus aureaus, Escherichia coli, Candida albicans and Pseudomonas aeruginosa. The assay consisted of dispersing the inoculum across the surface of the plates and subsequent application of discs containing AgNPs at a concentration of 1.0 mmol/L. The formed halos were measured with the aid of a caliper in millimeters. The results show that with changes in the color of the solution in visible ultraviolet UV-Vis spectroscopy, there was formation of AgNPs and indicated antimicrobial activity against Staphylococcus aureus strains. However, they did not show inhibitory activity against Pseudomonas aeruginosa and Escherichia coli and also did not show growth inhibitory activity against the tested fungus. It is concluded that AgNPs have antimicrobial potential against Staphylococcus aureus. Therefore, they must be tested on other microorganisms with other concentrations, as well as being applied in other technological and health areas, such as tissue regeneration.